2017
DOI: 10.1177/1060028017734234
|View full text |Cite
|
Sign up to set email alerts
|

Population Pharmacokinetics of Enoxaparin in Pediatric Patients

Abstract: Pediatric patients should initially be dosed at 1-mg/kg/dose subcutaneously every 12 hours for treatment of thromboembolism followed by anti-Xa activity monitoring. Dose reductions of ~30% for creatinine clearance ≤30 mL/min/1.73 m are required.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 26 publications
(41 reference statements)
1
14
0
Order By: Relevance
“… 6 , 7 Two population PK models of enoxaparin in children have been published which use allometrically scaled Wt as a covariate on clearance. 5 , 17 However, when both models were fitted to our dataset and evaluated using pcVPCs overlaid with the data, they performed well overall but significantly underpredicted concentration in the overweight/obese group (see Figure 3 ). This is probably due to CL being overestimated as a result of the assumption of proportionality to Wt.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“… 6 , 7 Two population PK models of enoxaparin in children have been published which use allometrically scaled Wt as a covariate on clearance. 5 , 17 However, when both models were fitted to our dataset and evaluated using pcVPCs overlaid with the data, they performed well overall but significantly underpredicted concentration in the overweight/obese group (see Figure 3 ). This is probably due to CL being overestimated as a result of the assumption of proportionality to Wt.…”
Section: Discussionmentioning
confidence: 91%
“… 3 , 4 A recent population analysis showed that this dose has a 72.3% probability of achieving the aXa concentration target in hospitalised paediatric patients. 5 Maintenance dosing based on total body weight (Wt) implies that enoxaparin clearance is linearly proportional to Wt. However, this has often been found to be inaccurate in overweight/obese individuals.…”
Section: Introductionmentioning
confidence: 99%
“…Based on adult data on enoxaparin with a creatinine clearance (CrCL) of <30 mL/min should have an empiric dose adjustment to 1 mg/kg daily. 3 In a pharmacokinetic study of enoxaparin in pediatric patients published by Moffett et al, 4 a 30% reduction in starting dose was recommended in patients with a CrCL of <30 mL/min. Given the limited available information, and by taking a more conservative approach, the dose was reduced to 1 mg/kg daily, which was a 50% reduction.…”
Section: Discussionmentioning
confidence: 99%
“…LMWH, mainly enoxaparin, is the primary choice for pediatric patients because of its stable pharmacokinetics and greater bioavailability [ 102 ]. A pharmacokinetic study of enoxaparin in children and adolescents proposed an initial dose of 1.0 mg/kg subcutaneously and every 12 h thereafter [ 103 ]. Although the recommendation for LMWH drug monitoring is the target anti-Xa activity [ 101 , 104 ], a recent retrospective cohort study showed that the proposed guidelines did not consistently lead to therapeutic anti-Xa levels [ 105 ].…”
Section: Management Of Pediatric Apsmentioning
confidence: 99%